ERROR DETECTION IN THE PROCESS OF DISPENSING OF INTERNAL MEDICINE AT A HOSPITAL PHARMACY OF SOCIAL SECURITY: Pharmaceutical SciencesPharmacy - B. R. LUGO, GLADYS; ROCÍO CONCEPCIÓN BLAIRES CARDOZO, JAZMÍN; H. MARIN, GUSTAVO; MORINIGO, MACARENA; SAMANIEGO, LOURDES; MAIDANA, MABEL (International Journal of Life Science and Pharma Research, 2017)
The present study aimed to identify errors in the process of dispensing drugs at the Internal Pharmacy of the Hospital Social Security, in Paraguay, South America. A descriptive observational study was designed, whose main variables were identification of errors and its classification according to international standards (LASA). The unit of analysis was recipes, which were aleatory chosen to be included in the study. The data collection tool consisted in a file record specially prepared for this purpose, in order to characterize and evaluate the detected errors. 1349 recipes performed during the period of the study were analyzed. There were detected 85 errors, which were classified according to LASA standards in errors caused by two major causes: similar package and similarity in medication’s sounding names. Both increased the possibility of errors either in fingering, dispensing, provision and administration of these drugs. Of all the mistakes committed, only one was due to an adverse drug reaction. The result of our work indicates that the prevalence of errors found was due to lack of care and training of health’s staff.